2020
DOI: 10.1371/journal.pone.0229769
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of menaquinone-4 (MK-4) on transient global cerebral ischemia/reperfusion injury in rat

Abstract: Cerebral ischemia/reperfusion (I/R) injury causes cognitive deficits, excitotoxicity, neuroinflammation, oxidative stress and brain edema. Vitamin K2 (Menaquinone 4, MK-4) as a potent antioxidant can be a good candidate to ameliorate I/R consequences. This study focused on the neuroprotective effects of MK-4 for cerebral I/R insult in rat's hippocampus. The rat model of cerebral I/R was generated by transient bilateral common carotid artery occlusion for 20 min. Rats were divided into control, I/R, I/R+DMSO (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 101 publications
5
24
1
Order By: Relevance
“…Hyperperfusion, which is considered as the hallmark of successful recanalization, may result in reperfusion injury [39]. Reperfusion injury may also be linked to excitotoxicity, neuroinflammation, oxidative stress, apoptosis and brain oedema [40,41], which might lead to neurological deterioration. Furthermore, END after endovascular treatment may be related to the procedure itself [38].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperperfusion, which is considered as the hallmark of successful recanalization, may result in reperfusion injury [39]. Reperfusion injury may also be linked to excitotoxicity, neuroinflammation, oxidative stress, apoptosis and brain oedema [40,41], which might lead to neurological deterioration. Furthermore, END after endovascular treatment may be related to the procedure itself [38].…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB has been regarded as one of the most important regulatory factors of the inflammatory cascade in renal IRI as it potentially regulates post-IRI cell survival. Various studies have shown that IRI promotes the local or systemic release of pro-inflammatory cytokines, such as TNF-α and IL-6, thereby aggravating organ injury ( Wei et al, 2019 ; Farhadi Moghadam and Fereidoni, 2020 ) Farhadi Moghadam and Fereidoni, 2020 Wei et al, 2019 . Therefore, renal IRI can be alleviated by suppressing the renal ischemia-induced inflammatory response ( Kasimsetty et al, 2020 ; Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…These include targeted ion channels, transporters, and specific targets. Also include anti-apoptotic, anti-inflammatory, and antioxidant drugs (Tan et al, 2019 ; Moghadam and Fereidoni, 2020 ; Yang et al, 2020 ). The Sur1-Trpm4 inhibitors are of particular interest and have been studied in three clinical trials.…”
Section: Perspectivesmentioning
confidence: 99%